Towards a Sociology of Innovation Ecosystems: Decision-Making under Uncertainty between Social Construction and Bounded Rationality - D'Alessandro, Simone (Italian Sociological Review, 2022)
Starting from the Schumpeterian approach and arriving at the most recent anti-mainstream theories on Innovation Ecosystems, the research examines, through theories, models and business cases, the problematic relationships between Innovation, Invention, and Creative Processes in an attempt to understand, from a sociological perspective, the decision-making processes induced by expectations and uncertainties. Different schools of thought in economics, agree that innovation is the main driver of growth. Disagreement arises when economists attempt to explain how innovation occurs, as there is a lack of shared understanding about the expectations of its decision-makers and implementers. There is also a lack of understanding about the social and cultural constructions of decision-makers, which are influenced by conditions of uncertainty, error and “non-knowledge” (Gross, McGoey, 2015).The imagined innovation may be considered feasible in the start-up phase but fail during its development. The innovator, in an ex-ante phase, cannot predict how a new hypothesis will evolve. In many cases, as we shall see, he will remove the observation of obstacles, because he is influenced by beliefs and convictions that disregard rational choices, even bounded ones.